Análisis del comportamiento de las principales exportaciones primarias e industrializadas en Ecuador - Ávila Cruz, Kevin Alexander (2022)
In Ecuador, foreign trade, over time, has been characterized by the quality of its primary and industrialized products; in recent years exports have been consolidating and placing themselves in a better positioning in foreign markets, non-oil primary products (shrimp, fish, cocoa, coffee, bananas and bananas) have been having a wonderful behavior as well as the industrialized (wood, mining products, canned fish and flowers) has been compared with its main competitors at a global level, hence the importance of carrying out an analysis of the behavior of non-oil and industrialized exports, how the rules and agreement of exports to Ecuador have been helping. The research aimed to analyze the behavior and variation of these exports. The method used is mixed, which allows to show the variation of the products as time passes. Which leads us to conclude that exports of non-oil primary and industrialized products played a significant role within the scope of exports in Ecuador, In addition, these products aim at transformation and destination with the sole purpose of growing and expanding, giving a product with the highest quality standards and the high concentration of economic activity in the foreign trade sector.